Infusing Health Disparities Awareness Into Public Health Curricula at a Rural Midwestern University - Njoku, Anuli; Wakeel, Fathima (Pedagogy in Health Promotion, 2019)
Preventable differences in health outcomes between U.S. population subgroups, related to factors such as race or ethnicity, income, and geographic location, are troubling. Geographically, rural American communities experience higher rates of adverse health conditions when compared with urban areas, further widening disparities in health outcomes. Such disparities necessitate the creation of effective curricula to enable students to address the health needs of underserved populations. By intentionally incorporating health disparities awareness content into the curricula, undergraduate and graduate public health programs can play an integral role in developing conscious health practitioners to help close gaps in health outcomes. Moreover, rural health courses may increase students’ interest in rural health careers. This article presents the process and results of faculty efforts to design and deliver health disparities–related education in undergraduate and graduate public health courses at a rural Midwestern U.S. university. Various teaching development programs inspired faculty to use intentional instructional approaches to teach students about health disparities. Consequently, faculty incorporated a variety of assessment methods and teaching styles to infuse health disparities awareness content into public health courses. Results from students’ course evaluations and reflections are discussed along with lessons learned and implications for future pedagogical directions.
Keywords: dept.pch; peer-reviewed